STRATEGI GURU DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN 39 PALEMBANG - Efriyanti, Ela; Boty, Middya; Tasya Jadidah, Ines (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine teacher strategies for increasing student learning engagement in fourth-grade science studies at SD Negeri 39 Palembang. This study used a qualitative approach with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects consisted of a fourth-grade teacher and fourth-grade students. The results showed that teacher strategies for increasing student learning engagement were implemented through the use of cooperative learning models, the use of learning media, and providing motivation and appreciation to students. These strategies were able to increase students' courage in asking questions, answering questions, discussing, and participating during the learning process. Supporting factors in the implementation of teacher strategies were the availability of learning media, student interest in learning, and a supportive school environment. Inhibiting factors included a lack of concentration on the part of some students and differences in student learning abilities. Based on the results of the study, it can be concluded that teacher strategies play a crucial role in increasing student learning engagement in fourth-grade science studies, thus making the learning process more active and effective. Keywords: Teacher strategies, Learning Engagement, Science Studies Learning.